(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Most ESBL Extended-Spectrum beta-lactamases (ESBLs) producing isolates carry TEM and SHV type betalactamases. Among these two types beta-lactamases SHV type was reported nosocomial infection outbreak in many countries in the world. The goal of this study was to see the rate of ESBLs production and also to detect SHV gene in those isolates recovered from a tertiary care hospital. A total of 354 samples were collected from Sir Salimullah Medical College and Mitford Hospital and from Burn Unit of Dhaka Medical College Hospital from January 2011 to December 2011. To detect ESBLs, Gram-negative organisms were subjected to Double Disc Synergy Test and SHV gene was detected from those ESBLs producing microorganisms by PCR. In this study, out of 354 different clinical samples 186 (89%) were Gram-negative organisms. Among of these Gramnegative organisms 77 (41.40%) were ESBL producing isolates detected by Double Disc Synergy Test. Out of these 77 isolates, 8 isolates (10.38%) carried bla SHV gene. Among those ESBL producing 26.26% Klebsiella spp. (4 out of 15 isolates) had SHV gene. Our findings showed that the majority of the ESBLs positive clinical isolates were Klebsiella spp. and high frequency of SHV genes were found in Klebsiella spp. Bangladesh J Med Microbiol 2014; 08 (02): 14-18